Vitamin D supplementation in adolescent female ballet dancers and gymnasts in a 12 month randomised controlled trial in Auckland, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Jessup, Wendy (Massey University, 2014)
Aim: To examine the effects of vitamin D supplementation on the bone health of female adolescent ballet dancers and gymnasts. Method: Adolescent female ballet dancers and gymnasts from Auckland, New Zealand were recruited to a 12 month randomised double-‐blind trial. Participants were supplemented with cholecalciferol 50,000 IU per month or a placebo. At baseline detailed dietary intake was collected by a four day food record; at baseline and 12 months bone mineral density (BMD) and content were recorded by DXA as well as bone-‐free, fat-‐free, lean body mass, percentage body fat, height and weight. At baseline, six months and 12 months serum markers for vitamin D (oestradiol and parathyroid hormone) were collected. Results: A total of 61 adolescent girls were recruited at baseline, BMD and content by DXA was completed in 45 girls and 41 provided vitamin D serum samples. Serum vitamin D concentration was recorded for 41 female ballet dancers and gymnasts aged 12 to 18 years was 72 nmol/L and remained adequate (>50 nmol/L) in both intervention and control groups for the 12 month duration. There was no significant difference between intervention and control groups in bone mineral density and content at any bone site at 12 months. The significant predictors of increased bone mineral density at baseline were older age (P=0.002) higher bone-‐free, fat-‐free, lean body mass (P=0.001) and higher calcium intake (P=0.005). For higher bone mineral content the significant predictors at baseline were older age (P=0.01) and higher bone-‐ free, fat-‐free, lean body mass (P=0.001). In all participants (n=48) bone mineral density and content increased significantly at 12 months (total body BMD and content, areal BMD, total hip BMD and content, femoral neck BMD and content and lumbar spine BMD and content). II Discussion: More than adequate baseline serum vitamin D levels in this adolescent group may explain the lack of significant difference in any of the bone measures between intervention and control groups. As the age range of the adolescent girls varied markedly and older age predicted both an increase in BMD and content, it is likely that there was also bone accrual due to growth. The nil effect of vitamin D supplementation on bone measures was also limited by the small sample size. Conclusion: In this study vitamin D supplementation had no effect on the bone mineral density and content of female adolescent ballet dancers and gymnasts. Further investigations are needed to examine vitamin D supplementation on bone measures in a large group of adolescent girls.
Keywords: Teenage ballerinas; Adolescent ballerinas; Female gymnasts; Adolescent gymnasts; Vitamin D in nutrition; Vitamin D supplementation